Narrativas de un Grupo de Parejas de la Localidad Rafael Uribe de Bogotá sobre las Estrategias de Afrontamiento frente a situaciones conflictivas que les permitieron mantenerse unidas durante el Confinamiento por el Covid -19 (2023)
The main objective of the research was to understand the narratives and experiences of a group of couples from the Rafael Uribe town of Bogotá about the coping strategies in the face of conflictive situations that allowed them to stay together during the confinement caused by Covid19, for which contexts related to the main theme were described, based on the narratives indicated by the couples participating in the study.